1999
DOI: 10.1542/peds.103.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Parents, Physicians, and Antibiotic Use

Abstract: Pediatricians acknowledge prescribing antimicrobial agents when they are not indicated. Pediatricians believe educating parents is necessary to promote the judicious use of antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
145
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(155 citation statements)
references
References 20 publications
2
145
1
7
Order By: Relevance
“…Prior research suggests that a more informed public will make fewer demands for unnecessary antibiotics. [3][4][5] As a result, the Centers for Disease Control and Prevention (CDC), in collaboration with universities, pharmaceutical companies, health delivery systems, and other partners, developed the "Public Action Plan to Combat Antimicrobial Resistance." 6 As part of this effort, the CDC provides program support for several campaigns around the United States that are focusing on promoting appropriate antibiotic use.…”
mentioning
confidence: 99%
“…Prior research suggests that a more informed public will make fewer demands for unnecessary antibiotics. [3][4][5] As a result, the Centers for Disease Control and Prevention (CDC), in collaboration with universities, pharmaceutical companies, health delivery systems, and other partners, developed the "Public Action Plan to Combat Antimicrobial Resistance." 6 As part of this effort, the CDC provides program support for several campaigns around the United States that are focusing on promoting appropriate antibiotic use.…”
mentioning
confidence: 99%
“…In another study, when asked to identify the single most important program to reduce inappropriate antibiotic use in children, 78% of surveyed by guest on May 9, 2018 http://pediatrics.aappublications.org/ Downloaded from pediatricians indicated that educating parents about the judicious use of the antibiotics would be most efficacious. 18 We need effective techniques for educating parents about the judicious use of antibiotics. The American Academy of Pediatrics, the Centers for Disease Control and Prevention, and the American Society of Microbiology have developed an educational pamphlet entitled "Your Child and Antibiotics" for distribution in health care providers' offices.…”
mentioning
confidence: 99%
“…When pressured to prescribe these medications, 30% of pediatricians reported complying with this request "occasionally" or more frequently. 18 The effect of perception of parental expectations for antibiotics on physician behavior is striking. Mangione-Smith et al 19 found that private practice pediatricians prescribed antibiotics to 52% of children who were 2 to 10 years of age and presenting with URI symptoms and received a diagnosis of a viral illness when the physician reported that she or he perceived that the parent desired these medications versus 9% when he or she did not have this perception.…”
mentioning
confidence: 99%
“…Other studies included educational interventions for both parents and physicians had promising results. [17][18] However, only a few studies assessed the changes with regard to specific diagnoses, as was done in this study. Smabrekke et al 19 noted a reduction in antibiotic prescriptions for AOM, from 90% to 74%, and also a reduction in broad-spectrum antibiotic use, after an educational intervention addressing physicians and parents.…”
Section: Discussionmentioning
confidence: 99%